Systems engineering and analysis - Blanchard, Benjamin S.; Fabrycky, W. J. (Wolter J.) 1932- (Pearson, 2014)
This practical introduction to systems engineering and analysis provides the concepts, methodologies, models, and tools needed to understand and implement a total life-cycle approach to systems and their analysis.